POLICY ON THE USE OF SOCIAL MEDIA IN HOSPITALS IN BUILDING COMMUNICATION DURING THE COVID-19 PANDEMIC: LITERATURE REVIEW - Kumalasari, Rita; Sulistiadi, Wahyu (Journal of Indonesian Health Policy and Administration, 2022)
Social media is necessary for almost everyone, including in health services. During the COVID-19 pandemic, social media was widely used to build hospital communications. However, the benefits come with risks, as communication spreads so quickly. A proper policy is needed. This study aims to determine the benefits of social media in building communication in hospitals and the policies that govern it. The method used is a literature study. A literature search, through Science Direct, ProQuest, Google Scholar, and other databases (Google scholar, NIH/NLM, JMIH), with the keywords "social media" AND "communication" AND “policy” AND "hospital" AND "COVID-19 Pandemic", obtained 520 articles completely. According to the inclusion, exclusion, and duplication selection criteria, there were twelve included articles. The results prove that social media plays a role in hospital internal and external communication. The use of social media, in addition to improving hospital communication with all employees, also plays a role in improving communication between hospitals and patients, especially in providing information, telemedicine, helping health promotion to change behavior, influencing patient visits, overcoming limited facilities and access and as a new method that efficient way to reach bigger people during the COVID-19 pandemic. However, a policy that regulates the use of social media is needed. Guidelines based on the principles of maintaining patient privacy and confidentiality, providing correct information, conveying the source of contact information in every information submitted, using clear language, and verifying data.